A study of error diversity in robotic swarms for task partitioning in foraging tasks - Buchanan, Edgar; Alden, Kieran; Pomfret, Andrew; Timmis, Jon; Tyrrell, Andy M. (Frontiers in Robotics and AI, 2023)
It is often assumed in swarm robotics that all the robots in the swarm behave virtually the same, and will have a similar (if not the same) error model. However, in reality, this is not the case and this lack of uniformity can lead to unexpected emergent behaviours. This paper compares the impact of robots in a swarm having the same error model (uniform error) against each robot in the swarm having a different error model (error diversity). Experiments are presented in the context of a foraging task. Simulation and physical experimental results in this paper show the importance of the error model and diversity in achieving expected swarm behaviour.